2005
DOI: 10.1007/s10029-005-0331-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon perspectives on options for ventral abdominal wall hernia repair: results of a postal questionnaire

Abstract: This survey shows a lack of consensus on the appropriate repair of ventral abdominal wall hernia among practicing consultant general surgeons. This reflects the contrasting views within the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Dalenbäck (21) suggested a tailored repair and stated that suture-based methods for defects <2 cm can provide acceptable recurrence rates (6%) in long-term follow-up. A postal questionnaire study from Scotland revealed that surgeons preferred mesh repair for defects >5 cm, whereas similar preference rates for suture and mesh repairs were obtained for defects <2 cm (22).…”
Section: Which Repair Technique?mentioning
confidence: 85%
“…Dalenbäck (21) suggested a tailored repair and stated that suture-based methods for defects <2 cm can provide acceptable recurrence rates (6%) in long-term follow-up. A postal questionnaire study from Scotland revealed that surgeons preferred mesh repair for defects >5 cm, whereas similar preference rates for suture and mesh repairs were obtained for defects <2 cm (22).…”
Section: Which Repair Technique?mentioning
confidence: 85%
“…Currently there is no consensus regarding the best approach to incisional hernia repair. [21,22] Our survey of practicing surgeons echoes this lack of consensus. We identified a median utilization rate of less than ten percent for the laparoscopic approach with respondents indicating that they believe the results are not better than the open repair.…”
Section: Discussionmentioning
confidence: 85%
“…Despite this, our survey has a greater number of respondents than previous survey studies of this subject. [20,21] The authors developed this survey instrument based on the concepts and controversies that were felt to be important in the decision to use or not use the individual techniques of ventral incisional hernia repair among surgeons. This study surveyed opinions and perceptions of surgeons and was not designed to identify which technique performs better in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Lichtenstein hernipoplasty comprises of the reduction of hernia contents followed by the strengthening of the posterior wall of inguinal canal (fascia transversalis) without disturbing the anatomy and creation of a new internal ring. 4 The standard way of anchoring the mesh to the posterior wall is with polypropylene suture. 5,6 This study was conducted to find out effectiveness of anchoring the mesh in position using the stainless steel skin staples.…”
Section: Patients Above 18 Year Of Age Who Underwent Inguinal Hernia mentioning
confidence: 99%